Faktor-Faktor Yang Mempengaruhi Korupsi Berdasarkan Teori Fraud Triangle Pada Novel 86 Karya Okky Madasari - Aan Saputra; Hilmy Darul Fadilah; Eva Dwi Kurniawan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research aims to determine the factors that cause corruption using the fraud triangle theory in literary media. The literary work that will be used as a source of research data is the novel entitled "86" by Okky Madasari. The problem that will be presented is about what factors influence the occurrence of corruption using the fraud triangle theory in the novel "86". This research is a type of qualitative research using the hermeneutic method or interpreting the meaning of the text. The conclusions obtained from this research are the results of the analysis carried out on the novel "86" by Okky Madasari, which shows the factors that cause acts of corruption, namely pressure, opportunity and justification.